Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fbuil.2022.1018395
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the relationship between VOCs emission and temperature/humidity changes in new apartments in the hot desert climate

Abstract: Much previous research in different countries describes a strong dependence on temperature and humidity for indoor air pollutants generated from building materials. Since many types of building materials are complexly applied in residential buildings in UAE and are constantly using air-conditioning, the result might be different from the characteristics of indoor air pollutants from a small chamber experiment. This paper aims to investigate the relationship between the concentration of indoor air pollutants ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Ultimately, this study focuses on the measurement and analysis of HCHO and total volatile organic compounds (TVOC), which are known to be the main causes of SBS in IAQ (Jung, Mahmoud and Alqassimi, 2022). The research specifically targets newly constructed apartments at Ajman Al Jurf area.…”
Section: Ajman and Uae Building Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, this study focuses on the measurement and analysis of HCHO and total volatile organic compounds (TVOC), which are known to be the main causes of SBS in IAQ (Jung, Mahmoud and Alqassimi, 2022). The research specifically targets newly constructed apartments at Ajman Al Jurf area.…”
Section: Ajman and Uae Building Standardsmentioning
confidence: 99%
“…Ajman is currently the fifth The Effects of Hazardous Substances on the Human. Adapted from(Jung, Mahmoud and Alqassimi, 2022).…”
mentioning
confidence: 99%
“…The emission of VOCs and formaldehyde can be influenced by various factors such as temperature and relative (Cheng et al, 2022). Chuloh et al (2022) reported that an increase in humidity tends to increase the level of VOCs concentrations. According to the findings of Zhou et al (2019), an increase in relative humidity enhances the release of VOCs.…”
Section: Effects Of Atmospheric Properties (Relative Humidity and Tem...mentioning
confidence: 99%
“…Third, the thermal decomposition of materials can occur at higher temperatures, leading to the release of additional VOCs [28]. Finally, higher temperatures can lead to increased humidity levels, which can enhance the release of VOCs from some materials [29].…”
Section: Influence Of Temperature On Tvoc Emissionsmentioning
confidence: 99%